FREEZEWAVE – Innovative and low energy microwave assisted freezing process for high quality foods - Xanthakis, Epameinondas; LeBail, Alain; Shrestha, Marie; Ahrne, Lilia; Bernard, Jean-Paul (My University, 2015)
FREEZEWAVE project proposes a highly innovative technique which showed that a small amount of emitted microwave energy combined to a slow freezing rate is able to refine ice crystal size in frozen meat. FREEZEWAVE project aims at expanding & optimizing the concept to several foods and also at designing industrial equipment. Herein, the structure and the directions of the project as well as the initial results of this study and the preliminary results of the previous study will be illustrated. More specifically, the application of microwaves during cooling the samples caused oscillated decrease of temperature and had a significant impact on the crystallization process as the degree of supercooling was decreased circa 92% under the tested conditions. The meat microstructure evaluation showed a 62% decrease in the average ice crystal size when samples were frozen under a microwave field as compared to the conventional freezing process.
Keywords: Microwave energy; Ice crystal size; Frozen meat